Design para confiança: a experiência do usuário com o banco digital - Santos, Rodrigo dos (Universidade do Vale do Rio dos Sinos, 2018)
Due to the new technologies developed in recent years, there have been changes in the behavior and experience of user relationships with financial institutions. Breakthrough technologies such as smartphone applications, which offer the same services available in a bank branches, could eliminate personal banking relationships in the coming years. With this, there is the possibility of the users' behavior with these new services of the so-called "digital bank", awaking experiences that may influence the construction of trust in the banking relationship. Thus, considering the design for emotion an area that studies projects with the purpose of provoking or avoiding certain emotions, a research was carried out to evaluate and understand the construction of users' trust in the use of digital channels for relationship with financial institutions. In order to do so, this work contextualized the current banking market and the future projection, realizing the deepening of themes related to emotions, design for emotions and a cognitive theory used by the area of design, Appraisals Theory, with the objective of understanding how, from appraisals of events and situations, results in the emotion of trust, which interferes in the relationship of consumers with the digital bank based on the concerns (attitudes, beliefs and learned patterns) of the people. The research was carried out based on a qualitative and exploratory study. Twenty-four interviews were carried out with users of banking financial services to identify their appraisals and concerns regarding the use of digital banks, and the comments was analyzed through the Content Analysis technique. The study turned possible to understand the triggers related to emotions, which lead to the formation of confidence to use the digital channels of financial institutions and, from them, to establish design guidelines for the designer's work.
Keywords: Design emocional; Teoria dos Appraisals; Experiência; Tecnologia; Banco digital; Design for emotion; Appraisal Theory; User experience; Technology; Digital bank; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial